PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI PERSON ORGANIZATION FIT (Study Aparatur Sipil Negara Pada RSUD Dr. H Soewondo Kabupaten Kendal) - Aprillia Herdhiyani, 1352020033; Yulianto, Heru (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research aimed to examine the effect of leadership, motivation on employee performance with mediation person-organization fit for the job. The study was conducted by taking samples Apparatus State Civil Hospital Dr. H. Soewondo Kendal who have the status of civil servants with tenure of more than 5 years old, at least high school education and have a minimum rank class IIa. The sampling technique used is the purposive sampling method and probability sampling stratified random sampling to obtain the number of respondents 148 employees. The statistical method used is Multiple Linear Regression assisted by SPSS version 19. The results of this study indicate a positive and significant influence between the leadership of the person-organization fit, there is positive and significant correlation between motivation of the person-organization fit, there is positive and significant between motivation on employee performance, there is a positive and significant influence between person-organization fit on employee performance. While the leadership has no significant negative effect on employee performance.Keywords: Leadership, Motivation, Performance, Person Organization Fit